Bilateral versus unilateral instrumentation in spinal surgery: Systematic review and trial sequential analysis of prospective studies. (August 2016) - Phan, Kevin; Leung, Vannessa; Scherman, Daniel B.; Tan, Andrew R.; Rao, Prashanth J.; Mobbs, Ralph J.
Highlights: Bilateral and unilateral instrumentation in spinal surgery were compared. Meta-analysis and trial sequential analysis (TSA) were used. No difference in fusion and complication rates found. Similar post-operative Visual Analog Scale back/leg pain and Oswestry Disability Index scores were found. TSA suggests further studies will not significantly alter observed trends. Abstract: Lumbar fusion surgical intervention is often followed by bilateral pedicle screw fixation. There has been increasing support for unilateral pedicle screw fixation in an attempt to reduce complications and costs. The following study assesses the efficacy and complications of bilateral versus unilateral pedicle screw fixation in open and minimally invasive lumbar interbody fusion techniques. A systematic review with meta-analysis and trial sequential analysis was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and recommendations. In comparison with existing meta-analyses, trial sequential analysis was implemented to reduce the potential for type I error. Of the 1310 citations screened, four observational studies and 13 randomised controlled trials were used comprising 574 bilateral cases and 549 unilateral cases. Statistical analysis showed no difference in fusion rates, total complications, dural tear rates, Visual Analogue Scale (VAS) score for back pain, VAS for leg pain, Oswestry Disability Index scores, and length of stay between bilateral and unilateral instrumentation. Unilateral instrumentation was significantly shorter in duration (P < 0.00001) and led to significantly lower blood volume loss (P = 0.0002). These results were the same for both open and minimally invasive surgical approaches. Unilateral pedicle screw fixation appears to have similar post-operative outcomes as bilateral fixation and improved efficacy in regards to procedure duration and blood volume loss.